Effects of ozone therapy on anxiety and depression in patients with refractory symptoms of severe diseases: a pilot study - Clavo, Bernardino; Cánovas-Molina, Angeles; Díaz-Garrido, Juan A.; Cañas, Silvia; Ramallo-Fariña, Yolanda; Laffite, Horus; Federico, Mario; Rodríguez-Abreu, Delvys; Galván, Saray; García-Lourve, Carla; González-Beltrán, Damián; Caramés, Miguel A.; et al. (Frontiers in Psychology, 2023)
Background Patients with refractory symptoms of severe diseases frequently experience anxiety, depression, and an altered health-related quality of life (HRQOL). Some publications have described the beneficial effect of ozone therapy on several symptoms of this kind of patient. The aim of this study was to preliminarily evaluate, in patients treated because of refractory symptoms of cancer treatment and advanced nononcologic diseases, if ozone therapy has an additional impact on self-reported anxiety and depression. Methods Before and after ozone treatment, we assessed (i) anxiety and depression according to the Hospital Anxiety and Depression Scale (HADS); (ii) the HRQOL (according to the EQ-5D-5L questionnaire), which includes a dimension on anxiety and depression and a visual analog scale (VAS) measuring self-perceived general health. Results Before ozone therapy, 56% of patients were on anxiolytic and/or antidepressant treatment. Before and after ozone therapy, the anxiety and depression HADS subscales (i) significantly correlated with the anxiety/depression dimension of the EQ-5D-5L questionnaire and (ii) inversely correlated with the health status as measured by the VAS. After ozone therapy, we found a significant improvement in anxiety and depression measured by both the (i) HADS subscales and (ii) EQ-5D-5L questionnaire. Conclusion The addition of ozone therapy for patients with refractory symptoms of cancer treatment and advanced chronic nononcologic diseases can decrease anxiety and depression severity levels. Additional, more focused studies are ongoing to provide the needed explanatory information for this finding.